2016
DOI: 10.1038/srep36335
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration and energy shortage in the suprachiasmatic nucleus underlies the circadian rhythm disturbance in ApoE−/− mice: implications for Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) patients suffer sleep disorders and circadian rhythm disturbances (CRDs). The underlying mechanisms are incompletely understood, and treatments are lacking. In this study, we characterized the locomotor activity, clock gene expression, morphological degeneration and energy metabolism of suprachiasmatic nucleus (SCN), together with retinal light sensing, in ApoE−/− mice, a model for AD. Compared with the control C57BL/6J mice, ApoE−/− mice exhibited disordered circadian locomotor activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 44 publications
2
31
2
Order By: Relevance
“…Additionally, Alzheimer's disease is characterized by, most notably, deficits in learning and memory and impairments of activities of daily living. In mice, activities of daily living are commonly examined via circadian wheel-running 8,9,10,11 , although new alternatives, such as nesting, are growing in popularity. Nesting has been shown to be sensitive to manipulations (e.g., genetic mutations, environmental stressors) that have been identified as risk factors and/ or causes of Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Alzheimer's disease is characterized by, most notably, deficits in learning and memory and impairments of activities of daily living. In mice, activities of daily living are commonly examined via circadian wheel-running 8,9,10,11 , although new alternatives, such as nesting, are growing in popularity. Nesting has been shown to be sensitive to manipulations (e.g., genetic mutations, environmental stressors) that have been identified as risk factors and/ or causes of Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction or loss of circadian rhythms can result from aging and neurodegeneration, and oxidative stress plays a central role in the pathological processes of both (Bellanti et al., ; Fifel, ; Li, Wang, Wang, Hu, & Liu, ; Liu & Chang, ; Stevanovic et al., ; Van Erum et al., ; Wang et al., ; Wilking et al., ; Zhou et al., ). Studies indicate that Cu accumulates in specific brain regions of aged subjects (Braidy et al., ; Fu, Jiang, & Zheng, ; Pushkar et al., ; Singh et al., ; Wang, Becker, et al., ; Zatta et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Another, conducted in an animal model of "jetlag", showed that the animals exposed to circadian cycle disruption exhibited diminished hippocampal neurogenesis and impaired learning and memory, as well as increased blood inflammatory markers 9 . However, one of the best pieces of evidence underlying the circadian rhythm disruption in AD patients and the sundown syndrome is the degeneration of the suprachiasmatic nucleus 61 .…”
Section: Potential Mechanisms Linking Sleep Disorders and Ad Riskmentioning
confidence: 99%